2010
DOI: 10.1007/s11104-010-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the potential role of metals in sugar maple (Acer saccharum Marsh) decline in Ontario, Canada

Abstract: Spatial and temporal differences in the crown condition of sugar maple (Acer saccharum Marsh) in Ontario remain largely unexplained. In this study, the potential role of metals in sugar maple dieback was explored by measuring metal concentrations in foliage and forest floor (LFH) at 35 forest stands in south-central Ontario that exhibit varying levels of decline and span a climatic, soil acidity and acid deposition gradient. Foliar and forest floor metal concentrations varied among sites by between two and ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…vitality remains a major concern in many areas of the northeastern North America, including New York (Hallett et al, 2006), Pennsylvania (Long et al, 1997(Long et al, , 2009(Long et al, , 2011Horsley et al, 2000Horsley et al, , 2002Bailey et al, 2004), the New England states of New Hampshire and Vermont (Wilmot et al, 1995(Wilmot et al, , 1996Hallett et al, 2006;Schaberg et al, 2006;Gavin et al, 2008) in the USA as well as Quebec (Duchesne et al, , 2003Duchesne and Ouimet, 2008;Ouimet, 2006, 2010;Ouimet et al, 2008) and Ontario (Ryan et al, 1994;McLaughlin, 1998;McLaughlin et al, 2000;Watmough and Dillon, 2003;Tominaga et al, 2008;Watmough, 2010) in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vitality remains a major concern in many areas of the northeastern North America, including New York (Hallett et al, 2006), Pennsylvania (Long et al, 1997(Long et al, , 2009(Long et al, , 2011Horsley et al, 2000Horsley et al, , 2002Bailey et al, 2004), the New England states of New Hampshire and Vermont (Wilmot et al, 1995(Wilmot et al, , 1996Hallett et al, 2006;Schaberg et al, 2006;Gavin et al, 2008) in the USA as well as Quebec (Duchesne et al, , 2003Duchesne and Ouimet, 2008;Ouimet, 2006, 2010;Ouimet et al, 2008) and Ontario (Ryan et al, 1994;McLaughlin, 1998;McLaughlin et al, 2000;Watmough and Dillon, 2003;Tominaga et al, 2008;Watmough, 2010) in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is unsurprising that many studies on SM dieback suggested that base cation deficiency, and particularly Ca deficiency, was a cause of the tree growth reduction and decline (Sharpe and Sunderland, 1995;Wilmot et al, 1995;Long et al, 1997Long et al, , 2009Bailey et al, 2004;Schaberg et al, 2006;Huggett et al, 2007;Watmough, 2010). Moreover, a positive growth and vigor response of SM to liming or Ca addition in base-poor northern hardwood stands demonstrated that the Ca deficiency was linked to SM decline in these ecosystems (Wilmot et al, 1996;Ouimet, 2006, 2010;Juice et al, 2006;Huggett et al, 2007;Ouimet et al, 2008;Long et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soil acidity (pH) restricts the availability of essential macro-nutrients, leading to root mortality and eventually dieback (Houle et al 2007;Watmough 2010). Studies such as those of (Burke & Raynal 1998;Duchesne et al 2002) have indicated that soil acidification restricts the availability of plant macronutrients, leading to root mortality, nutrient deficiency and eventually tree dieback.…”
Section: Soil Aciditymentioning
confidence: 99%
“…Drought conditions have caused increased soil salinity, thereby potentially contributing to massive die-off of the salt marshes in southern United States (Silliman, 2005). In addition, soil acidity (pH) restricts the availability of essential macro-nutrients, leading to root mortality and eventually dieback in sugar maple, Acer saccharum (Houle et al 2007;Watmough 2010). In blackberry (Rubus anglocandicans) decline in Western Australia, flooding events is considered as a predisposing factor and this stress condition makes blackberries susceptible to root pathogen infection (Aghighi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Forest or watershed liming can also provide long-term neutralization of surface water. Although this technique is not yet widely used in operational settings, forest liming has received growing interest due to the need for mitigation tools to counteract the decreasing vitality and productivity of sugar maple dominated stands observed in many areas of northeastern North America over the last decades (Wilmot et al 1996;Horsley et al 2002;Hallett et al 2006;Bailey et al 2004;Schaberg et al 2006;Gavin et al 2008;Tominaga et al 2008;Long et al 2009Long et al , 2011Watmough 2010;Moore et al 2012). This has also provided a better understanding of the role of calcium and pH in these ecosystems.…”
Section: Liming Of Forest and Aquatic Ecosystemsmentioning
confidence: 99%